Pengelolaan Sumber Daya Alam Hutan Studi Kasus : Hutan Kota Tinjomoyo Kota Semarang - Timoro, Paskhalis B.; Perkasa, Yuvens D.; Wibowo, Bonifasius B.S.; Kurniawan, Thomas A.; Ismail, Amrizarois (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Forest is a stable ecosystem, which has a balance between producers, consumers and decomposers. Where, the forest itself has the ability to provide unlimited natural resources. However, optimal and sustainable forest management and utilization is needed in order to have a forest that has adequate environmental carrying capacity, with the aim of guaranteeing the role and existence of the forest. The Tinjomoyo City Forest which is located in Semarang City has an area of ​​57 ha, with the area of ​​green space in Semarang City being 10,966 ha, out of the 37,367 ha area of ​​Semarang City. Thus, it has reached 30% of the need for green space in the City, if based on Law no. 41 of 1999. Therefore, because the position of the City of Semarang, which has a large green space, has complied with the Law, it is very important to maintain its existence. In this research, it was carried out by direct observation method, which included observation, inventory, and volume calculation. After carrying out an inventory and data processing, it was found that the Tinjomoyo City Forest had a volume of wood reserves of 4,548,600 m3. So with the knowledge of these large enough wood reserves, it is necessary to maintain, manage and utilize forest resources optimally and sustainably. With the aim, to maintain the availability of wood reserves in the Tinjomoyo City Forest.